2004
DOI: 10.1128/aac.48.5.1600-1613.2004
|View full text |Cite
|
Sign up to set email alerts
|

Functional Genomic Analysis of Fluconazole Susceptibility in the Pathogenic Yeast Candida glabrata : Roles of Calcium Signaling and Mitochondria

Abstract: The pathogenic yeast Candida glabrata exhibits innate resistance to fluconazole, the most commonly used antifungal agent. By screening a library of 9,216 random insertion mutants, we identified a set of 27 genes which upon mutation, confer altered fluconazole susceptibility in C. glabrata. Homologues of three of these genes have been implicated in azole and/or drug resistance in Saccharomyces cerevisiae: two of these belong to the family of ABC transporters (PDR5 and PDR16), and one is involved in retrograde s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
162
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(170 citation statements)
references
References 71 publications
8
162
0
Order By: Relevance
“…An ecm7 mutant of yeast was one of many mutants reported with general cell wall defects (39). Additionally, an ecm7 mutant of the pathogenic yeast C. glabrata was one of several reported with hypersensitivity to the azole-class antifungal agent fluconazole (9). The Ecm7 proteins and their roles in Ca 2ϩ uptake have not been previously studied.…”
Section: Yellow Symbols)mentioning
confidence: 99%
“…An ecm7 mutant of yeast was one of many mutants reported with general cell wall defects (39). Additionally, an ecm7 mutant of the pathogenic yeast C. glabrata was one of several reported with hypersensitivity to the azole-class antifungal agent fluconazole (9). The Ecm7 proteins and their roles in Ca 2ϩ uptake have not been previously studied.…”
Section: Yellow Symbols)mentioning
confidence: 99%
“…Interestingly, in contrast to C. albicans, most of the investigations carried out in different regions of the world have revealed that point mutations within the ERG11 gene of azole-resistant C. glabrata isolates are rarely identified or are not present at all (Berila & Subik 2010;Berila et al, 2009;Sanguinetti et al, 2005). There also exist many other possible, not fully recognized mechanisms affecting C. glabrata resistance to azoles, such as mitochondrial dysfunction (Ferrari et al, 2011) and calcium signalling (Kaur et al, 2004). However, they do not seem to be as important as overexpression of drug efflux proteins or enzymes involved in ergosterol synthesis (Rodrigues et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The means Ϯ standard deviations of data from two biological replicates are shown for panels C and D. The means for each group were compared by using a two-tailed t test. *, P Ͻ 0.05. cellular Ca 2ϩ (29). Therefore, to determine if the vacuolar trafficking defects of the vps21⌬/⌬ mutant impact cellular Ca 2ϩ homeostasis, we compared the levels of intracellular free calcium using the calcium-responsive dye Fura 2-AM (30).…”
Section: Fig 1 the C Albicans Vps21⌬/⌬ Mutant Exhibits Less Membranementioning
confidence: 99%